Novel Serum Oxidative Stress Biomarkers in Pemphigus Vulgaris: Clinical Insights and Implications for Pathogenesis - Naglaa El Sayed; Dalia Halwag; Nesrine Ahmed Helaly; Iman Abdelmeniem (Dermatology Practical & Conceptual)
Introduction: Pemphigus vulgaris is an autoimmune disorder characterized by blistering of the skin and mucous membranes due to the loss of cohesion between keratinocytes. Oxidative stress, a condition caused by an excess of reactive oxygen species that overwhelms the body's antioxidant defenses, has been implicated in various autoimmune diseases, including pemphigus vulgaris.